2020
DOI: 10.1101/2020.04.10.20060558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydroxychloroquine in patients mainly with mild to moderate COVID–19: an open–label, randomized, controlled trial

Abstract: Objectives To assess the efficacy and safety of hydroxychloroquine (HCQ) plus standard-of-care (SOC) compared with SOC alone in adult patients with COVID-19.Design Multicenter, open-label, randomized controlled trial.Setting 16 government-designated COVID-19 treatment centers in China through 11 to 29 in February 2020.Participants 150 patients hospitalized with COVID-19. 75 patients were assigned to HCQ plus SOC and 75 were assigned to SOC alone (control group).Interventions HCQ was administrated with a loadin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
376
1
26

Year Published

2020
2020
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(409 citation statements)
references
References 26 publications
6
376
1
26
Order By: Relevance
“…Notably, results from an open-label, randomised, controlled trial using doses as high as HCQ 1200 mg for 3 days (followed by a maintenance dose of 800 mg daily for 2-3 weeks) did not suggest efficacy of HCQ in suppressing viral replication. 22 These efficacy data, and the irrefutable clinical data collected through the COVID-19 Global Rheumatology Alliance registry, establish that patients with lupus on baseline therapy with HCQ are not universally protected from COVID-19.…”
mentioning
confidence: 99%
“…Notably, results from an open-label, randomised, controlled trial using doses as high as HCQ 1200 mg for 3 days (followed by a maintenance dose of 800 mg daily for 2-3 weeks) did not suggest efficacy of HCQ in suppressing viral replication. 22 These efficacy data, and the irrefutable clinical data collected through the COVID-19 Global Rheumatology Alliance registry, establish that patients with lupus on baseline therapy with HCQ are not universally protected from COVID-19.…”
mentioning
confidence: 99%
“…One such randomized trial, DISCOVERY, has been launched in Europe and will compare the effectiveness of hydroxychloroquine plus standard of care versus standard of care alone and, in other arms of the study, the effectiveness of remdesivir, lopinavir plus ritonavir, and lopinavir plus ritonavir plus interferon beta (39). Interestingly, the results from a multicenter, open-label randomized trial of 150 patients in China treated with hydroxychloroquine versus SOC for 28 days did not demonstrate relief of symptoms and the hydroxychloroquine group reported significantly higher levels of side effects (30% versus 8.8%) (40). Treatment with hydroxychloroquine did, however, lower C-reactive protein (CRP) levels, thus supporting an anti-inflammatory action of the drug.…”
mentioning
confidence: 99%
“…Touret and de Lamballerie 15 CQ inhibits the replication of SARS-CoV in Vero E6 cells CQ can be highly effective against HCoV-OC43 infection in newborn mice Wang et al 16 CQ effective in vitro against isolates of 2019-nCOV Yao et al 17 HCQ is more potent than CQ against SARS-CoV-2 in vitro Gao et al 18 CQ effective at improving pneumonia exacerbation, findings on lung imaging, promoting virusnegative conversion, and shortening COVID-19 without serious adverse reactions Gautret et al 19 HCQ treatment is significantly associated with viral load reduction/disappearance in COVID-19 patients, and its effect is reinforced by azithromycin Lover 21 Reanalysis of Gautret et al 19 data shows HCQ monotherapy had modest to no impact on clearance of viremia, but HCQ + AZT showed more significant results Molina et al 22 HCQ + AZT showed no evidence of rapid antiviral clearance or clinical benefit in severe COVID-19 Tang et al 23 HCQ did not result in a higher negative conversion rate but more alleviation of clinical symptoms than SOC alone in patients hospitalized with COVID-19 without receiving antiviral treatment Chen et al 24 HCQ a baseline echocardiogram as well as liver and renal function. Noteworthy drug interactions include increased hypoglycemic risk with antidiabetic medications or insulin, increased risk of ventricular arrhythmia with arrhythmogenic drugs, and impaired efficacy of antiepileptic drugs.…”
Section: Current Evidencementioning
confidence: 99%